Transcriptome analysis and differential gene expression profiling of wucai (Brassica campestris L.) in response to cold stress - Wang, Chenggang; Zhang, Mengyun; Zhou, Jiajie; Gao, Xun; Zhu, Shidong; Yuan, Lingyun; Hou, Xilin; Liu, Tongkun; Chen, Guohu; Tang, Xiaoyan; Shan, Guolei; Hou, Jinfeng (BMC genomics, 2022)
Background Wucai suffers from low temperature during the growth period, resulting in a decline in yield and poor quality. But the molecular mechanisms of cold tolerance in wucai are still unclear. Results According to the phenotypes and physiological indexes, we screened out the cold-tolerant genotype “W18” (named CT) and cold-sensitive genotype “Sw-1” (named CS) in six wucai genotypes. We performed transcriptomic analysis using seedling leaves after 24 h of cold treatment. A total of 3536 and 3887 differentially expressed genes (DEGs) were identified between the low temperature (LT) and control (NT) comparative transcriptome in CT and CS, respectively, with 1690 DEGs specific to CT. The gene ontology (GO) analysis showed that the response to cadmium ion (GO:0,046,686), response to jasmonic acid (GO:0,009,753), and response to wounding (GO:0,009,611) were enriched in CT (LT vs NT). The DEGs were enriched in starch and sucrose metabolism and glutathione metabolism in both groups, and α-linolenic acid metabolism was enriched only in CT (LT vs NT). DEGs in these processes, including glutathione S-transferase s ( GST s), 13S lipoxygenase ( LOX ), and jasmonate ZIM-domain ( JAZ ), as well as transcription factors (TFs), such as the ethylene-responsive transcription factor 53 (ERF53), basic helix-loop-helix 92 (bHLH92), WRKY53, and WRKY54.We hypothesize that these genes play important roles in the response to cold stress in this species. Conclusions Our data for wucai is consistent with previous studies that suggest starch and sucrose metabolism increased the content of osmotic substances, and the glutathione metabolism pathway enhance the active oxygen scavenging. These two pathways may participated in response to cold stress. In addition, the activation of α-linolenic acid metabolism may promote the synthesis of methyl jasmonate (MeJA), which might also play a role in the cold tolerance of wucai.